2015
DOI: 10.5194/aab-58-151-2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and time of day of sampling on proximate and fatty acid composition of whole eggs from two strains of laying hens

Abstract: Abstract. The aim of the present study was to determine the effects of breed (Naked Neck -NN -and Lohmann Brown -LB), age (46 to 49 weeks) and the time of day of sampling (morning eggs -M -and afternoon eggs -A) on the proximate and fatty acid composition of whole eggs.Eggs of commercial hens (LB) had significantly (P < 0.001) less fat, ash and protein and lower dry-matter content (more water content) compared to the autochthonous breed (NN). The NN eggs contained significantly (P < 0.001) more SFA (saturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The results of this study, similar to those of previous studies, showed that palmitic, oleic, and linoleic acids were the most abundant fatty acids in eggs (Hidalgo et al 2008, Samman et al 2009, Stanišić et al 2015. SFA levels were similar in eggs produced by both organic and conventional production systems, which is in agreement with the results of Cherian et al (2002).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study, similar to those of previous studies, showed that palmitic, oleic, and linoleic acids were the most abundant fatty acids in eggs (Hidalgo et al 2008, Samman et al 2009, Stanišić et al 2015. SFA levels were similar in eggs produced by both organic and conventional production systems, which is in agreement with the results of Cherian et al (2002).…”
Section: Discussionsupporting
confidence: 92%
“…Pintea et al (2012) demonstrated that egg yolk lipids in Araucana hens had a lower SFA content, a higher MUFA, EPA and DHA content, and a more favourable n-6/n-3 ratio than the egg yolk lipids of ISA Brown hens. Stanišć et al (2015) did not confirm the effect of breed on the percentage of n-3 fatty acids. Rizzi and Marangon (2012) showed the effect of breed on the fatty acid profile of yolks in organic eggs and found the egg yolks from Hy-Line Brown hens to contain less saturated fatty acids, less monounsaturated fatty acids and more polyunsaturated fatty acids compared to the eggs of the other breeds.…”
Section: Vitamins Cholesterol and Fatty Acids In Yolkmentioning
confidence: 78%
“…Significantly higher (p<0.01) egg white to yolk ratio of Tetra SL hens (2.04) compared to hens of Banat Naked neck (1.54) and Svrljig hens (1.45) indicates a significantly higher share of yolks in eggs of native breeds of hens. It is known that native breeds of hens accumulate higher fat deposits compared to hybrid layers (Stanišić et al, 2015), which is associated with differences in productivity of these layers (Rizzi and Chiericato, 2010). The more intense coloration of egg yolks of Polish native hens (Sokolowicz et al, 2018) in the free range system compared to hybrid layers from the same systems, as well as Czech hen (Svobodova et al, 2014) in the cage and floor breeding system, confirm the effect of genotype, in accordance with our results, and indicates that this trait of yolk quality is not necessarily related to the availability of pastures, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative production systems have long been in the focus of researchers, as well as finding opportunities for the self-sustainability of native, indigenous breeds through the production of biologically valuable food. In this regard, research on local native breeds of hens is increasingly present, both in terms of morphological and production characterization (Milošević et al, 2013;Teneva et al, 2015), and in terms of various aspects of product quality (Pavlovski et al, 2011;Mitrović et al, 2011;Stanišić et al, 2015), while few studies (Pavlovski et al, 2012;Sokolowicz et al, 2018) investigate the physical characteristics of egg quality of native hen breeds.…”
Section: Introductionmentioning
confidence: 99%